Book Review on Hosting Capacity for Smart Power Grids, Ahmed F. Zobaa, Shady H. E. Abdel Aleem et al. Springer, 1 2020 - Mousa, Hossam H. H.; Mahmoud, Karar; Lehtonen, Matti (Peneliti Teknologi Teknik Indonesia, 2024)
Nowadays, the growing integration of new industrial technologies into modern power systems (MPSs) such as distributed energy resources (DERs) such as various types of renewable energy sources (RESs), electric vehicles (EVs), and energy storage systems (ESSs), caused various adverse impacts that should be considered broadly. These technologies cause various deteriorations on the performance indices (PIs), e. g. voltage deviation and reverse power flows. Therefore, the hosting capacity (HC) concept is declared to ensure that integration is managed efficiently to accommodate them without any PI violations. Various research fields investigated HC technologies in terms of calculation methods, tools, enhancement techniques, etc. in several articles and books. However, the book entitled “Hosting Capacity for Smart Power Grids, Ahmed F. Zobaa, Shady H.E. Abdel Aleem et al. Springer, 1 2020”, is the most recent prominent comprehensive reference for HC strategies in MPSs. Hence, this article proposes a book review and discussion of its most important contributions which helps the reader in realizing the recent developments in HC technologies based on this book’s contents.